In situ growth of 2D BiOI precursors on a porous conductive framework for a high performance bismuth based aqueous battery. Issue 27 (5th July 2021) - Liu, Pengfei; Zhang, Xiaodong; Feng, Liping; Pan, Haixi; Yang, Beining; Zheng, Xiaoqi; Dong, Guangzhi
Abstract : In this work, a porous conductive framework (PCF) was constructed and high performance Ni3 S2 //Bi aqueous battery was assembled based on the PCF. Abstract : Aqueous bismuth based anodes have received intensive interest in recent years. However, further advances in rate capability and cycling stability remain challenging. Herein, a porous conductive network is first constructed to accommodate the dense growth of 2D BiOI nanosheets, which served as an appropriate precursor of Bi active materials. Benefiting from the porous conductive 3D framework and in situ topotactic transformation of ultrathin BiOI nanosheets, favorable reaction kinetics and effective utilization of active materials are achieved. The resultant binder-free bismuth anode shows a prominent areal capacity (2.17 mA h cm −2 at 1 mA cm −2, 1.48 mA h cm −2 at 128 mA cm −2 ), long-term stability (93.1% retention after 5000 cycles) and high mass loading of 27 mg cm −2 . The mechanism regarding cycling stability is revealed by DFT calculations. In addition, the assembled Ni3 S2 //Bi full battery exhibits a high energy density of 22.73 mW h cm −3 . Considering the facile preparation process and impressive performance of the device, this work proposes a general strategy for constructing advanced aqueous batteries and shows the great potential of bismuth based anodes in large-scale applications.